Identification and Conservation Status of Birds Traded in Bird Shops in Kuranji District, Nanggalo District, East Padang District, South Padang District, and Lubuk Begalung District, West Sumatra - Saputra, Anugra; Mauliza, Rani; Naibaho, Rikarlina Br; Yopiando, Yopiando; Solehah, Nur Hajijah; Pratama, Sandi Fransisco; Satria, Rijal (Jurnal Biologi Tropis, 2024)
Indonesia is a country with the highest diversity in the world. One of Indonesia's diversity is birds. Birds have many roles in maintaining the balance of nature. However, as birds become more popular every year, many birds are hunted and traded freely. This has an impact on the natural imbalance caused by the decline in bird populations and even the extinction of birds. The purpose of this study is to identify the species and conservation status of birds traded in Padang City, West Sumatra. This study is a descriptive study with a field survey method in several bird shops spread across several sub-districts in Padang City, West Sumatra. The results of the identification of the conservation status of birds traded in the city of Padang, West Sumatra used the IUCN red list website. Based on the data, as many as 25 out of 34 species of birds that have been identified have the Least Consern conservation status.